Pengaruh Otonomi Daerah terhadap Pengembangan Pondok Pesantren di Kabupaten Jember: The Impact of Regional Autonomy on the Development of Islamic Boarding Schools in Jember Regency - Miftah Arifin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2006)
Since 2001, Indonesia’s implementation of regional autonomy has shifted significant governance responsibilities to local authorities, yet its impact on traditional Islamic education institutions remains underexplored. This study investigates how regional autonomy influences the development of pondok pesantren in Jember Regency, focusing on educational, economic, and human resource dimensions. Using a qualitative approach with purposive sampling, data were collected through in-depth interviews with government officials, religious leaders, pesantren administrators, and students, as well as documentary analysis. Findings reveal that despite increased local government authority and various material and non-material aid programs—such as funding, skills training, and health services—regional autonomy has not significantly altered the vision, mission, or operational status of pesantren. Most pesantren continue to operate independently, showing little perceived benefit from autonomy policies. Administrators possess only a superficial understanding of regional autonomy laws, and government assistance often lacks targeting and coordination. The study concludes that regional autonomy has yet to produce meaningful impacts on pesantren development and recommends systematic accreditation, data-driven classification, and closer collaboration between local government and the religious affairs office to ensure equitable and effective support. Penerapan otonomi daerah di Indonesia sejak tahun 2001 telah mengalihkan wewenang pemerintahan yang signifikan kepada pemerintah daerah, namun dampaknya terhadap lembaga pendidikan Islam tradisional masih jarang diteliti. Penelitian ini mengkaji pengaruh otonomi daerah terhadap pengembangan pondok pesantren di Kabupaten Jember, dengan fokus pada aspek pendidikan, ekonomi, dan sumber daya manusia. Menggunakan pendekatan kualitatif dengan sampel purposif, data dikumpulkan melalui wawancara mendalam dengan pejabat pemerintah, tokoh agama, pengelola pesantren, dan santri, serta analisis dokumenter. Temuan menunjukkan bahwa meskipun terjadi peningkatan kewenangan pemerintah daerah dan berbagai program bantuan material maupun non-material—seperti dana, pelatihan keterampilan, dan layanan kesehatan—otonomi daerah belum secara signifikan mengubah visi, misi, atau status operasional pesantren. Sebagian besar pesantren tetap berjalan mandiri dan tidak merasakan manfaat nyata dari kebijakan otonomi. Para pengasuh pesantren hanya memahami otonomi daerah secara dangkal, dan bantuan pemerintah sering kali tidak tepat sasaran serta kurang terkoordinasi. Penelitian ini menyimpulkan bahwa otonomi daerah belum memberikan dampak berarti terhadap pengembangan pesantren, dan merekomendasikan akreditasi sistematis, klasifikasi berbasis data, serta kolaborasi erat antara pemerintah daerah dan kantor agama untuk memastikan dukungan yang merata dan efektif.